Leadership Styles of Women Leaders in Panchayati Raj Institutions - Kaur, Manmeet; Bhardwaj, Neelam; Bareth, L. S. (Indian Journal of Extension Education, 2017)
Women leadership in Panchayati Raj Institutions (PRI) is crucial not only for the development of women themselves  but also for the availability of their creative potential that is socially important and without which, the country cannot  hope for any sustainable development. This study was conducted in three districts of Uttarakhand State i.e. Udham  Singh Nagar, Dehradun and Tehri Garhwal districts on two hundred women leaders especially Pradhans who were  selected through census method. Data were collected with the help of semi-structured interview schedule. The  findings of the study depict that there was very slight difference found in each category of leadership style.  Authoritarian leadership style was more prominent in the Udham Singh Nagar whereas participative and delegative  styles were followed by women leaders who belonged to hill districts of Uttarakhand. Various socio-psychological  and communication pattern characteristics were found positively and significantly related with leadership styles of  women leaders.
Keywords: Leadership styles; Women leaders; Panchayati Raj Institutions (PRIs)